Feminism Reality as Expressed by Sumarni in the Years of The Voiceless Novel by Okky Madasari: A Critical Discourse Analysis - Ayu Monita Eka Shinta (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2018)
This thesis entitled Feminism Reality as Expressed by Sumarni in theYears of the Voiceless Novel by Okky Madasari: A Critical Discourse Analysis isconducted to convey position and feminism reality of woman as reflected bySumarni in this novel. The subject of this study is the main character namelySumarni regarded as a voiced civilian woman. The reason for choosing this novel isbecause of inequality power relation issues, especially woman. Women areconsidered as weak. Here, Sumarni appears as a main character who wants tospeak up rather than to be voiceless. This study is intended to give a model in howwoman can show her power through her utterances since woman wants to be equalin society. There were several steps in doing this study which have been done.Under the qualitative research, the data collection started from reading the noveland then selecting utterances. While the method of data analysis was done bygrouping Sumarni’s utterances, after that the utterances were analyzed byconsidering feminist stylistic elements at the level of sentence by using transitivitychoices and Wodak’s triangulatory approach. The result of this study reveals thatthe use of relational process is higher than material process intention andsupervention, and mental process internalized and externalized. From the findingabove, it can be seen that Sumarni appears as a not common woman since she canbe a sugarcane field owner and moneylender in the end of the novel. In addition,there is a feminism reality as realized by Sumarni that a woman must beindependent and be responsible both in society and family. Keywords: CDA, feminist stylistics, feminism, The Years of the Voiceless,utterancesWomen